New Insight on Antibiotic Resistance and Virulence of Escherichia coli from Municipal and Animal Wastewater - Gabriela Gregova; Vladimir Kmet; Tatiana Szaboova (MDPI AG, 2021)
Antibiotic resistance of the indicator microorganism Escherichia coli was investigated in isolates from samples collected during the course of one year from two wastewater treatment plants treating municipal and animal wastes in Slovakia, respectively. The genes of antibiotic resistance and virulence factors in selected resistant E. coli isolates were described. A high percentage of the isolates from municipal and animal wastewater were resistant to ampicillin, streptomycin, tetracycline, ceftiofur, ceftriaxone, and enrofloxacin. In the selected E. coli isolates, we detected the following phenotypes: ESBL (20.4% in animal wastewater; 7.7% in municipal wastewater), multidrug-resistant (17% of animal and 32% of municipal isolates), high resistance to quinolones (25% of animal and 48% of municipal samples), and CTX-M (7.9% of animal and 17.3% of municipal isolates). We confirmed an integro-mediated antibiotic resistance in 13 E. coli strains from municipal and animal wastewater samples, of which the Tn3 gene and virulence genes cvaC, iutA, iss, ibeA, kps, and papC were detected in six isolates. One of the strains of pathogenic E. coli from the animal wastewater contained genes ibeA with papC, iss, kpsII, Int1, Tn3, and Cit. In addition, one blaIMP gene was found in the municipal wastewater sample. This emphasises the importance of using the appropriate treatment methods to reduce the counts of antibiotic-resistant microorganisms in wastewater effluent.